PE11 (Rv1169c) selectively alters fatty acid components of Mycobacterium smegmatis and host cell interleukin-6 level accompanied with cell death - Deng, Wanyan (Frontiers in Microbiology, 2015)
PE/PPE family proteins, named after their conserved PE (Pro-Glu) and PPE (Pro-Pro-Glu) domains of N-terminal, are most intriguing aspects of pathologic mycobacterial genome. The roles of most members of this family remain unknown, although selected genes of this family are related to the virulence of Mycobacterium tuberculosis. In order to decipher the role of Rv1169c, the Mycobacterium smegmatis strain heterologously expressed this ORF was constructed and identified that Rv1169c was a cell wall associated protein with a novel function in modifying the cell wall fatty acid component.. The growth of Rv1169c expressing strain was affected under surface stress, acidic condition and antibiotics norfloxacin and rifampicin treatment. M. smegmatis expressing Rv1169c induced necrotic cell death of macrophage after infection and significantly decreased interlukin-6 production compared to controls. In general, these results underscore a proposing role of Rv1169c in virulence of M. tuberculosis, as it’s role in the susceptibility of anti-mycobacteria factors caused by modified cell wall fatty acid, and the induced necrotic cell death by Rv1169c is crucial for M. tuberculosis virulence during infection.